The Role of Flouting Maxim, Context of Situation and Its Function in Supporting Elle Woods’ Character Development in the Legally Blonde (2001) Movie - Shafa Afriela Yonika (Universitas Sebelas Maret, 2025)
This study explores how flouting maxims and social context contribute to the character development of Elle Woods in Legally Blonde (2001). It identifies the types and strategies of flouting used, examines their illocutionary functions, and analyzes their role across different stages of the narrative. Using a qualitative, pragmatic approach and Spradley’s ethnographic analysis, 123 utterances from the movie script were analyzed. Elle was found to flout all four maxims—quantity, quality, relevance, and manner—using strategies like overstatement, sarcasm, and ambiguity. These often occurred in high power and high distance contexts (+P +D), with relevance being the most flouted. The dominant illocutionary function was competitive. The findings show that Elle’s use of flouting maxims shifts alongside her growth, highlighting their role in portraying her transformation from a stereotypical